Effect of 6-hydroxydopamine blockade of sympathetic nerves on systemic inflammation in an imiquimod-induced psoriasis-like mouse model - Siqi LIU; Yurong LUO; Yu PENG; Yingping XU; Yunsheng LIANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To explore the effect of 6-hydroxydopamine blockade of sympathetic nerves on systemic inflammation in an imiquimod(IMQ)-induced psoriasis-like mouse model. Methods Twenty-four SPF C57BL/6J mice were randomly divided into psoriasis-like dermatitis model group (model group), Candida albicans infected group, blank control group, psoriasis-like dermatitis model with vehicle treatment group (vehicle model group), 6-hydroxydopamine (6-OHDA) treated group, vehicle control group, with 4 mice in each group. The changes of lesion in each group were observed every day. Local inflammation in the dorsal and ear lesions of mice was detected by HE staining, q-PCR and Western blotting of interleukin 17A(IL-17A). Spleens of mice were taken to detect inflammatory cells by flow cytometry, and the level of interleukin 6(IL-6) and interleukin 1β(IL-1β) were detected by q-PCR and Western blotting for the systemic inflammation. Results Epidermal thickening, hypokeratosis, basal keratinocyte proliferation, inflammatory cell infiltration and IL-17A increasing were observed on the dorsal lesions of mice in the Candida albicans infection group and the psoriasis-like model group. Compared with the Candida albicans infected group, there were a large number of skin scale production and spleen enlargement, and splenic inflammatory cells increased, the level of IL-6, IL-1β increased in the psoriasis-like model group. Compared with the solvent model group, the spleen in the 6-OHDA treated group was smaller, the number of macrophages derived from neutrophils and monocytes in the spleen was significantly decrease, and the levels of IL-6 and IL-1β in the spleen were significantly lower. Conclusions IMQ-induced psoriasis-like mouse model lead to systemic inflammation, which can be caused by excessive sympathetic activation.